(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Questions: What is the composition of the spontaneous and cultivated plants in the flora of the "Synytsky Park" (Cherkasy Region) and does it reflect the stages of its development? Location: “Synytsky Park”, Synytsya village, Uman district, Cherkasy Region, Ukraine. Methods: a critical review of literature and historical sources, field observations and structural analysis. Nomenclature: POWO 2024 Results: The article provides information on dendrological and floristic features of the ancient park-monument of landscape gardening of local importance “Synytsky Park” (Uman district, Cherkasy Region). The core of the park’s plantations consists of old ash (Fraxinus excelsior) stands, accompanied by Fagus sylvatica, Larix sibirica, Picea obovata, and Tilia americana var. heterophylla. A total of 263 age-old trees representing 19 species were identified in the park’s plantations. Dendrochronological data indicate that the main forest massif of the park was established during 1880–1900. The flora of the park comprises 388 taxa of spontaneous and cultivated plants from 75 families. The spontaneous flora includes 326 species and subspecies, among which 234 are native, and 92 are alien taxa. Among alien plants, xenophytes (61.3 %) predominate over ergasiophygophytes (38.7 %). The geographical structure of the spontaneous flora is dominated by wide-ranging species (60.3 %), with a notable presence of European (13.3 %) and European-sub- Mediterranean (19.3 %) species. The alien fraction of the flora is composed of species with different geographical origins. In terms of biomorphological structure, the aboriginal fraction of the flora is dominated by perennial herbaceous plants (59.2 %), whereas short-life herbaceous plants prevail in the alien fraction (62.0 %). The ecological and coenotic structure is primarily characterized by sylvants (30.0 %). Several ergasiophygophytes demonstrate features of invasive plants within the park, including: Acer negundo, Cornus sanguinea subsp. australis, Morus alba, Parthenocissus vitacea, and Salix × fragilis. For the first time, Chenopodium ucrainicum, Lonicera xylosteum, and Vitis labrusca were reported for the park’s territory. The naturalization of species such as Crataegus × media and Picea abies (as evidenced by selfseeding), as well as Menispermum dauricum, Tilia americana var. heterophylla, and Toxicodendron rydbergii (which reproduce vegetatively in their cultivation sites), requires further monitoring. Conclusions: It has been found that the tree plantations of the “Synytsky Park” are artificial, including almost all 263 trees of 19 species, which have an estimated age of 100–150 years. In total, 388 taxa of spontaneous and cultivated plants were registered in the territory of the “Synytsky Park”. New localities of Chenopodium ucrainicum, Lonicera xylosteum and Vitis labrusca – plants that are not common in Cherkasy Region were discovered.